How Do Investments in Financial Assets Affect the Financial Performance of Pension Firms? Evidence from Nigeria - LINUS, Ginika Nnewogo; ABDULRAUF, Lukman Adebayo-Oke; GBADEBO, Adedeji Daniel; AKANDE, Joseph Olorunfemi (Universidad Francisco de Paula Santander, 2025)
Pension Fund Administrators (PFAs) play an essential part in the management of pension funds that guarantee retirees’ comfortability and welfare after life of active service years. The PFAs constantly encounter problems associated with investment decision making and optimization of financial performance of their invested assets classes to provide good returns for the payment of pension benefits. This paper analyses the impact of investment securities on the financial performance of pension funds in Nigeria. We considered a theoretical construct that demonstrate how assets holding drives the financial performance of pension funds. We examine each security invested in the portfolio of the PFAs – money market securities (MMS), federal government securities (FGS), mutual funds (MTF) and private equity fund (PEF) – incentivize return on investment (ROI) of the PFAs. We applied the autoregressive distributive lag (ARDL) on published information of National Pension Commission (PENCOM) covering 2007 to 2021. The findings revealed that investment in money market securities have a positive impact on short-term ROI (10.223, p value < 0.01) but a negative impact in the long run (-10.798, p < 0.01). Investment in FG security does not significantly affect ROI in either the short run or long term. Private equity fund investments exhibit no significant short-term impact but positively influence long-term ROI (1.460, p< 0.01). The mutual fund investments negatively impact short-term returns (-1.054, p< 0.01) but have a positive effect on long-term ROI (1.463, p< 0.01). This suggest that the money market securities yield short-term gains, while the private equity and mutual funds indicates a potent long-term investment tool for long-term growth. However, the FG securities appear not to show a significant influence on financial performance. This outcome, evidently, underscores the need for policy and regulations to investment make the PFAs more strategically position to improve retirees’ welfare. We offer that the PFAs should ensure more investment in money market assets with effective switching strategies, to target potential short-term gains, manage long-term risks by promoting mutual funds and private equity funds investments for improved long-term performance and ensure portfolio diversification to include securities may guarantee sustainable long-term returns.